Retraction Note: Xia-yu-xue decoction (XYXD) reduces carbon tetrachloride (CCl4)-induced liver fibrosis through inhibition hepatic stellate cell activation by targeting NF-κB and TGF-β1 signaling pathways - Cheng Liu; Xia Yuan; Le Tao; Zhuoan Cheng; Xiuqin Dai; Xia Sheng; Dongying Xue (BMC, 2022)
This article has been retracted. Please see the Retraction Notice for more detail: 10.1186/s12906-015-0733-1